Effects of Temperature Variations on Solar Cell Efficiency in Tanzania - Ali, Salma (American Journal of Physical Sciences, 2024)
Purpose: The aim of the study was to examine the relationship between air quality and respiratory health in urban environments Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on air quality and respiratory health in urban Brazil found that higher pollution levels were associated with increased respiratory diseases like asthma and COPD. Lower-income communities faced greater health risks due to poor air quality. The findings stress the importance of regulations and interventions to improve air quality and protect respiratory health in urban areas of Brazil. Unique Contribution to Theory, Practice and Policy: Environmental justice theory, the exposure-response theory & the social determinants of health theory may be used to anchor future studies on air quality and respiratory health in urban environments. Researchers should employ a combination of observational studies, longitudinal cohorts, and intervention trials to assess the impact of air quality on respiratory health outcomes in urban populations. Governments and policymakers should prioritize investments in clean energy technologies, sustainable transportation systems, and green infrastructure to minimize sources of air pollution and promote respiratory health in urban environments.